Thực trạng hạn hán ở các tỉnh Duyên hải Nam Trung Bộ và giải pháp phòng chống - Dân, Nguyễn Lập; Lan, Vũ Thi Thu (Vietnam Journal of Earth Sciences, 2012)
SUMMARY Situation of drought in central coastal provinces and anti solutions South Central Coastal provinces (including Quang Nam, Da Nang, Quang Ngai, Binh Dinh, Phu Yen, Khanh Hoa, Ninh Thuan and Binh Thuan) have an area of 40,655.7 km2 (equivalent to 12.5 % of total area of whole country). The article referred to the situation and causes for droughts in recent years. Thereby drought preventive measures are proposed, including : engineering solutions, non engineering solutions, drought forecasting and warnings, especially to propose policy solutions to help building management systems for drought, desertification in order to minimize damages to the South Central Coastal provinces.